Pul's. Klub direktorov . Pul's. Klub direktorov . Pulse. Directors' Club . Пульс. Клуб директоров - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Heads of enterprises discuss economic reforms. Featured in the program: Aganbegian, Abel Gezevich (Academician); Gerchikov, Vladimir Isakovich (Professor) Contributors: Kashkarova, Tamara (Anchor) Руководители предприятий обсуждают сущность и механизмы реализации экономических реформ. В программе участвуют: Аганбегян, Абел Гезевич (Академик); Герчиков, Владимир Исакович (Профессор) Создатели: Кашкарова, Тамара (Ведущий/Ведущая)